Film i dramat. "Śmierć i dziewczyna" Romana Polańskiego - Choczaj, Małgorzata (Wydawnictwo Naukowe UAM w Poznaniu; Wydawnictwo PWSFTViT w Łodzi, 2010)
Death and the Maiden by Roman Polański is an example of an experimental transposition of Ariel Dorman’s drama into the visual language of film. The merging of words and pictures in the film is compared to Bachtin’s dialogisation which permeates the element of the European novel. The meaning and motivation of the words in the characters’ dialogues influences the development of the action, form and rhythm of the takes as well as their juxtaposition with the characters and props. Polański does not limit himself only to a single-track effect. As dialogisation influences the forms of visualization, so images broaden the meanings of the dialogues, creating new contexts. The film is not only an attempt to prove that the alleged or real rapist was guilty, but also a study of the dishonoured woman’s fight for a right to live without traumatic reminiscences.
Keywords: drama and film; language of film; transposition; adaptation; dialogisation